The Reduction of the Arbëresh Lexicon and its Effects on Syntax - Turano, Giuseppina (Forum for Linguistic Studies, 2025)
The aim of this paper is to show how the loss of many lexical items in Arbëresh (a minority language genealogically and typologically related to Albanian and spoken in Southern Italy) has led to absence of the corresponding syntactic structures they project. This is the case, for example, of the conditional complementizer particles po, në, nëse, sikur, all corresponding to the English ‘if’. They are used in standard Albanian to introduce conditional subordinate sentences, some of which show the regular Subject-Verb-Object word order; others, instead, display V-second effects, caused by the movement of the verb to a position preceding the subject. These lexical items have completely ceased to be used in the Arbëresh dialects. Therefore, the syntactic structures typical of standard Albanian do not have their counterparts in the Arbëresh dialects, which employ only a structure similar to that of Italian, i.e. they have only a single conditional conjunction (corresponding to the Italian se ‘if’) projecting an unmarked embedded SVO sentence. Based on the distribution of topics in relation to these particles, I will argue that all these complementizers occupy an intermediate position in the left periphery of the clause. In particular, I will assume that they are associated with the CP domain, which is split into various positions in the sense of Rizzi.